Assessment of Nutrient Availability in Soil Textural Constituent as Influenced by Land Use - Oluwawemimo Omowumi Akingbola; Gabriel Olufemi Dayo-Olagbende; Felix Efeoghene Begusa; Babatunde Sunday Ewulo; Christopher Oluwakunmi Akinbile (Turkish Journal of Agriculture: Food Science and Technology)
Investigating the nutrient composition in soil textural constituent as influenced by land use is a necessity towards a good soil conservative and management measure. In view of this, a laboratory experiment was conducted; soil samples were collected from different locations within and outside the Federal University of Technology, Akure and analyzed for basic chemical elements. The soil sampling was based on land use and six different soil samples were collected at a depth of 0-15cm. These samples included bare soil (BS), waterlogged soil (WS), maize cultivated soil (MS), cassava cultivated soil (CS), cassava-maize intercrop (CM), and mixed cropping of cassava, maize and cowpea (MC). The waterlogged soil was cultivated to rice while the bare soil was not cultivated. The soil samples were air-dried and crushed after which fractionation was carried out using a three-layer sieve to separate the soil particles into different size of 2mm to 0.5mm (Sand), 0.5mm-0.05mm (Silt) and